2011
DOI: 10.1007/s00449-010-0506-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation of gene expression in Bacillus subtilis samples of fermentation replicates

Abstract: The application of comprehensive gene expression profiling technologies to compare wild and mutated microorganism samples or to assess molecular differences between various treatments has been widely used. However, little is known about the normal variation of gene expression in microorganisms. In this study, an Agilent customized microarray representing 4,106 genes was used to quantify transcript levels of five-repeated flasks to assess normal variation in Bacillus subtilis gene expression. CV analysis and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…According to Zhou et al (2011) the coefficient of variance (CV) between genes from one dataset to another is useful to assess variation, even when there are large differences in their means. Based on the biological variation in Bacillus subtilis gene expression, Zhou et al (2011) established a CV cut-off of 0.1, defining genes with CV > 0.1 as highly variable.…”
Section: Biological Variation In Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Zhou et al (2011) the coefficient of variance (CV) between genes from one dataset to another is useful to assess variation, even when there are large differences in their means. Based on the biological variation in Bacillus subtilis gene expression, Zhou et al (2011) established a CV cut-off of 0.1, defining genes with CV > 0.1 as highly variable.…”
Section: Biological Variation In Gene Expressionmentioning
confidence: 99%
“…Some authors have established a database pinpointing the most variable genes of (their) species of interest, e.g. for mice up to 3.3% of the gene expression was found varying between organs (Pritchard et al, 2001) and for the bacteria Bacillus subtilis 11% of the genes showed high variation between replicates (Zhou et al, 2011). Moreover, in e.g.…”
Section: Introductionmentioning
confidence: 99%